Remember the time. Issue 6 (4th December 2022) - van Es, Sam W.
Abstract : Like the ability of a fox to avoid the same snare twice, the plant Arabidopsis thaliana seems to be able to respond differently to an event it has previously encountered. Shrewdness is no surprising characteristic of a fox, but the comparison does invite the question: do plants possess memory? In this edition of Physiologia Plantarum, the article by Vyse et al. (2022) describes how Arabidopsis responds differently to cold‐stress, when encountering it for the first time (priming) and to a second similar stress after a memory phase (triggering). Arabidopsis seems to perceive the stress after triggering as a milder one and the authors postulate that the memory of the first occurrence of the stress reduces the amount of resources needed to cope with the cold‐stress a second time.